(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Myocardial lesions are a common form of cardiac pathology (CP) in children and are attracting increasing attention from pediatricians. Children from families with a hereditary burden of cardiac pathology show significant changes in lipid metabolism. These changes can be significantly aggravated by inflammatory changes in the myocardium and deserve special study.